Evaluation Of Growth And Yield Of Rice (Oryza Sativa L.) Under Different Fertilizer Management Options In Three Growing Ecologies - Anim, J.J. (University of Ghana, 2017)
Demand for rice from developing countries is steadily increasing, replacing most of the coarse grains and root crops as the major source of dietary calories. Food insecurity in many Africa countries is inevitable if efficient procedures for boosting productivity, decreasing cost of production, and protecting the environment are not taken into account. The per capita consumption of rice in Ghana is currently about 24 kg per annum. Consumption of rice will continuing to go up due to rapid population growth and urbanization as well as rice which has become one of the main staple foods of the country. Domestic production of this cereal has been less than consumption needs, due to low level of production as a result of farmers’ adherence to poor production practices, such as improper nitrogen fertilizer management practices which lead to inefficient use of the applied N. The blanket nitrogen application overlooks the dynamic soil N supply and crop N needs resulting in an inefficient N recovery, leading to low yield. The main objective of the study was to ascertain the best nitrogen management options in different rice growing ecologies for sustainable rice production. Pot and field experiments were carried out at the Soil and Irrigation Research Centre, University of Ghana, Kpong in 2016 and 2017 cropping seasons. The pot experiment was laid out in a randomized complete block design with five replications. Three levels of growing ecology (CS, IIR and AC) were combined factorially with three levels of nitrogen management (N2, N3 and N4) and a control (N1). The field experiment was laid out in a split plot design with three replications. Rice growing ecology was the main plot factor while nitrogen management was the sub-plot factor. The growing ecology treatments included; continuous submergence/irrigation (CS), intermittent irrigation (IIR) and aerobic soil condition (AC) while the nitrogen management treatments included no N fertilizer application (control, N1), 90 kg N/ha applied in two splits (N2) N management aided by Leaf Colour chart (N3) and Multi-split nitrogen application of the recommended rate (90 kg N/ha applied in five splits) (N4). Results from both experiments showed physiological nitrogen use efficiency (PNUE) and agronomic nitrogen use efficiency (ANUE) following the trend: N3>N4>N2. Rice yield from LCC managed N practice (5.51t/ha) and multi-split N application (6.60t/ha) was statistically similar in the field experiment. Continuous submergence and intermittent irrigated ecology produced similar grain yields of rice and were better than that of aerobic condition. The interaction CS x N4 produced the highest grain yield (6.84t/ha) but was however, statistical at par with IIR x N4 interaction. N3 and N4 gave statistically similar gross and net returns but the interaction between LCC managed N fertilizer and intermittent irrigation gave higher (GHC 30,922.00) net return than all the other interactions.
Thesis (MPhil)
Keywords: Growth; Yield Of Rice; Oryza Sativa L .; Fertilizer Management; Three Growing Ecologies